The Combination of Short Message Service Reminder and Diary to Improve Diet Compliance Undergoing Hemodialysis - Endriyan Mulyadi Justicia Waluyo; Ima Sukmawati; Irpan Ali Rahman; Yuliani Yuliani (Universitas Muhammadiyah Surakarta, 2023)
Dietary compliance with chronic kidney disease is one aspect that plays an important role as one of the keys to successful therapy, preventing worsening of the condition and rapid progression of the stage and uremic syndrome. Providing media such as diaries and SMS reminders is one method to increase compliance. Objective: The purpose of this study was to analyze the increase in dietary compliance of CKD patients after being given a diary and SMS reminder.The method in this study is using a quasi-experimental method with a pre-test and post-test case control design. The sample in this study amounted to 44 respondents who were divided into two groups. Samples were taken using accidental sampling technique. Data was collected using a diet compliance questionnaire. Data analyis was carried out by using paired t-test and an independent t-test. The study was conducted in March-April 2022. The results of the paired t-test showed that there was an increase in dietary compliance after the intervention with a p-value of 0,000. Independent t-test showed that there were differences in dietary and SMS reminder with a p-value 0,000. Conlusion Diary and SMS reminders are effective in increasing dietary compliance of cronic kidney disease patients undergoing hemodialysis.